2022
DOI: 10.1101/2022.01.12.476057
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Enhanced food motivation in obese mice is controlled by D1R expressing spiny projection neurons in the nucleus accumbens

Abstract: Obesity is a chronic relapsing disorder that is caused by an excess of caloric intake relative to energy expenditure. In addition to homeostatic feeding mechanisms, there is growing recognition of the involvement of food reward and motivation in the development of obesity. However, it remains unclear how brain circuits that control food reward and motivation are altered in obese animals. Here, we tested the hypothesis that signaling through pro-motivational circuits in the core of the nucleus accumbens (NAc) i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(6 citation statements)
references
References 72 publications
0
6
0
Order By: Relevance
“…In recent years, several studies have analyzed the role of the mediodorsal NAcSh in feeding 20, 23, 24 and revealed that activation of the dopamine receptor 1 expressing medium spiny neurons (D1-MSNs) 25, 26 projecting to the lateral hypothalamus (LH) 21, 24 or ventral tegmental area (VTA) 27 stops ongoing food consumption. However, other studies showed that D1-MSNs activity was enhanced during appetitive phase 28 as well as consumption 29 . Although temporally distinct phases of feeding behavior, such as food seeking, food evaluation and consumption, could potentially account for such discrepancy, the heterogeneity of NAc neurons 30 could underlie the discrepancies considering that different studies might have manipulated different neuron subtypes with opposing functions.…”
Section: Mainmentioning
confidence: 83%
See 4 more Smart Citations
“…In recent years, several studies have analyzed the role of the mediodorsal NAcSh in feeding 20, 23, 24 and revealed that activation of the dopamine receptor 1 expressing medium spiny neurons (D1-MSNs) 25, 26 projecting to the lateral hypothalamus (LH) 21, 24 or ventral tegmental area (VTA) 27 stops ongoing food consumption. However, other studies showed that D1-MSNs activity was enhanced during appetitive phase 28 as well as consumption 29 . Although temporally distinct phases of feeding behavior, such as food seeking, food evaluation and consumption, could potentially account for such discrepancy, the heterogeneity of NAc neurons 30 could underlie the discrepancies considering that different studies might have manipulated different neuron subtypes with opposing functions.…”
Section: Mainmentioning
confidence: 83%
“…The NAc is a critical component of the basal ganglion circuitry, which receives and integrates information from cortical and limbic regions for actions. Previous studies have linked feeding behavior to the NAcSh 20, 21, 24, 27, 28, 36 . D1-MSNs, but not D2-MSNs, provide the dominant source of accumbal inhibition to the LH and regulate complex feeding behaviors through LH GABA neurons 20, 28 .…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations